Organic loading rate: a promising microbial management tool in anaerobic digestion - Ferguson, Robert M. W.; Coulon, Frederic; Villa, Raffaella (Elsevier, 2016)
This study investigated the effect of changes in organic loading rate (OLR) and feedstock on the volatile fatty acids (VFAs) production and their potential use as a bioengineering management tool to improve stability of anaerobic digesters. Digesters were exposed to one or two changes in OLR using the same or different co-substrates (Fat Oil and Grease waste (FOG) and/or glycerol). Although all the OLR fluctuations produced a decrease in biogas and methane production, the digesters exposed twice to glycerol showed faster recovery towards stable conditions after the second OLR change. This was correlated with the composition of the VFAs produced and their mode of production, from parallel to sequential, resulting in a more efficient recovery from inhibition of methanogenesis. The change in acids processing after the first OLR increase induced a shift in the microbial community responsible of the process optimisation when the digesters were exposed to a subsequent OLR increase with the same feedstock. When the digesters were exposed to an OLR change with a different feedstock (FOG), the recovery took 7d longer than with the same one (glycerol). However, the microbial community showed functional resilience and was able to perform similarly to pre-exposure conditions. Thus, changes in operational conditions can be used to influence microbial community structure for anaerobic digestion (AD) optimisation. Finally, shorter recovery times and increased resilience of digesters were linked to higher numbers of Clostridia incertae sedis XV, suggesting that this group may be a good candidate for AD bioaugmentation to speed up recovery after process instability or OLR increase.
Keywords: Volatile fatty acids; Lactic acid; Glycerol; Grease waste; Synergistaceae